DC/AC fundamentals a systems approach - Floyd, Thomas L.; Buchla, David M. (Pearson, 2013)
For courses in Electronics and Electricity Technology DC/AC Fundamentals: A Systems Approach takes a broader view of DC/AC circuits than most standard texts, providing relevance to basic theory by stressing applications of dc/ac circuits in actual systems.